A comparison of methods for LTR-retrotransposon insertion time profiling in the Populus trichocarpa genome. Issue 1 (2nd January 2018) - Mascagni, F.; Usai, G.; Natali, L.; Cavallini, A.; Giordani, T.
Abstract: Two different methods of calculating insertion profiles of long terminal repeat (LTR) retrotransposons in the genome are compared, analysing six retrotransposon lineages in Populus trichocarpa . The first method consists of aligning the two long terminal repeats of an element and translating nucleotide differences into years, based on nucleotide synonymous substitution rate. The second method infers proliferation time profile of a group of retrotransposons by analysing pairwise genetic distances between reverse transcriptase (RT)-encoding sequences that belong to paralogous elements of the same group and translating them into insertion dates using the same mutation rate as for the first method. The two methods gave quite different results, probably because they are related to different populations of retrotransposons. The RT-based method can provide reliable insertion profiles; the method based on LTRs can be used to date individual elements and to obtain reliable profiles related to the most recent evolutionary periods. We suggest that both methods should be used to evaluate the dynamics of the retrotransposon component of a genome.